Reliģiski-filozofiski raksti, XXVI - (:unkn) unknown (LU Filozofijas un socioloģijas institūts, 2019)
Volume XXVI is dedicated to the themes discussed during the scientific conference Dynamic Asia: Shaping the Future that took place in Riga on 13–15 April 2018, and were further explored after this conference. The conference was organised in cooperation between the Latvian Society for the Study of Religions and the Baltic Alliance for Asian Studies. This event brought together more than 80 participants from 20 countries. The topics presented at the conference are reflected in the current volume. Many of these articles are dedicated to Japanese culture, where spiritual, material and routine aspects intermingle in all walks of life. The Far East topic is expanded in papers on Korea and South East Asia, while current matters of importance to the Islamic civilisation are treated in the context of the Near and the Far East by analysing the problems caused by modernisation (including Islamism and terrorism) and unveiling the true causes of these phenomena, clashing with the stereotypes perpetuated in international media. The papers consider matters that are exceptionally varied and diverse, but each of them brings us all towards a more profound understanding of different cultures, reasserts the importance of human spirituality in the self-contradictory turmoil of a unidimensional, materialistic, globalised world. This special issue of the journal sees the light of day thanks to the initiative of Professor Agnese Haijima, as well as the financial support of the Japan Foundation and the University of Latvia.
Religious-Philosophical Articles, XXVI
Reliģiski-filozofiski raksti, 26
Keywords: Asia; Indic Sciences; Contemporary Japanese Architecture; Buddhism; Traditional Chinese culture; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects